Farmer Resilience After Floods and Landslides - Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Emi Wuri Wuryaningsih; Fitrio Deviantony; Yeni Fitria (KHD-Production, 2022)
Floods and landslides are crisis conditions for farmers who have the potential to cause trauma. The capacity of farmers to deal with, overcome and change due to traumatic experiences varies throughout life. Resilience will form coping mechanisms and influence mental health. Method: This research is a descriptive study with a cross-sectional design. Questionnaires were given to 100 farmers. Resilience was assessed using The Connor-Davidson Resilience Scale (CD-RISC). Univariate statistical analysis to determine the proportion of resilience. Results: The mean resilience of farmers after a disaster is 95.72. Discussion: Resilience is a stable personality trait characterized by an individual's ability to rise again from negative experiences and the ability to adapt to continual changes in life. Farmers who are directly affected by a disaster are in a traumatic condition, so they are very vulnerable to stress. The mental endurance of each farmer is different, according to the influencing factors